The Digital House of Care: information solutions for integrated care. Issue 5 (17th October 2016) - Muirhead, Andrew; Ward, Derek George; Howard, Brenda
Abstract : Purpose: The purpose of this paper is to describe the development of a digital tool in an English county striving towards a vision of integrated information that is used to underpin an increasingly integrated future of health and social care delivery. Design/methodology/approach: It discusses the policy context nationally, the origins and implementation of the initiative, the authors' experiences and viewpoint highlighting key challenges and learning, as well as examples of new work undertaken. Findings: In all, 12 health and care organisations have participated in this project. The ability for local commissioners and providers of services to now understand "flow" both between and within services at a granular level is unique. Costs are modest, and the opportunities for refining and better targeting as well as validating services are significant, thus demonstrating a return on investment. Key learning includes how organisational development was equally as important as the implementation of innovative new software, that change management from grass roots to strategic leaders is vital, and that the whole system is greater than the sum of its otherwise in-silo parts. Practical implications: Data linkage initiatives, whether local, regional or national in scale, need to be programme managed. A robust governance and accountability framework must be in place to realise the benefits of such as a solution, and IT infrastructure is paramount. Social implications: Organisational development, collaborative as well as distributed leadership, and managing a change in culture towards health and care information is critical in order to create a supportive environment that fosters learning across organisational boundaries. Originality/value: This paper draws on the recent experience of achieving large-scale data integration across the boundaries of health and social care, to help plan and commission services more effectively. This rich, multi-agency intelligence has already begun to change the way in which the system considers service planning, and learning from this county's approach may assist others considering similar initiatives.